Disarming doomsday : the human impact of nuclear weapons since Hiroshima - Alexis-Martin, Becky (Radical geography., 2019)
Since before the first atomic bomb exploded over Hiroshima, the history of nuclear warfare has been tangled with the spaces and places of scientific research and weapons testing, armament and disarmament, pacifism and proliferation. Nuclear geography gives us the tools to understand these events as well as the extraordinary human cost of nuclear weapons. Disarming Doomsday explores the secret history of nuclear weapons by studying the places they build and tear apart, from Los Alamos to Hiroshima. It looks at the legacy of nuclear imperialism from weapons testing on Christmas Island and across the South Pacific, as well as the lasting harm this has caused to both Indigenous communities and the soldiers that were ordered to conduct tests. Tying these complex geographies together for the first time, Disarming Doomsday takes us forward, describing how geographers and geotechnology continue to shape nuclear war and imagining ways to help prevent it in the future. -- Provided by publisher.